1977
DOI: 10.1192/bjp.130.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Obsessional Personality Disorder and Remembering

Abstract: Patients suffering from obsessional personality disorder (anankasts) have been described as possessing 'superior memories', because of the detailed precision of their accounts. At the same time, such classical phenomena as doubt, checking and rumination imply faulty recall. This paradox is discussed, and some predictions drawn from a hypothesis regarding the cognitive charactteristics of obsessional disorder. Findings are presented which indicate that, by comparison with matched psychiatric controls, anankasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 2 publications
8
28
1
Order By: Relevance
“…This finding of an impaired verbal memory in compulsive checkers was not replicated by a second sample [10], A study [32] on memory for actions in OCD showed that obsessivecompulsive subjects have difficulties in the storage and restitution phases and not in the acquisition phase. This result is in line with Reed's [7] study, which places the OCD mem ory deficit at the reintegration stage of memo ry.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This finding of an impaired verbal memory in compulsive checkers was not replicated by a second sample [10], A study [32] on memory for actions in OCD showed that obsessivecompulsive subjects have difficulties in the storage and restitution phases and not in the acquisition phase. This result is in line with Reed's [7] study, which places the OCD mem ory deficit at the reintegration stage of memo ry.…”
Section: Discussionsupporting
confidence: 80%
“…Controlled studies showed the positive effect of behavioral therapy, cogni tive therapy and pharmacological treatment with serotonergic antidepressants [1,2], Sev eral studies reported cognitive dysfunction disturbances which could be related to abnor malities in prefrontal, caudate and cingulate areas suggesting a complex information pro cessing alteration [3][4][5][6]. Alterations in memo ry performance have been reported in four studies [7][8][9][10] but their results are not conver-gent. Methodological problems may explain these discrepancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was developed on the basis of two assumptions made with regard to obsessions and compulsions: (1) they are an exaggeration of normal thoughts and behaviors (Pitman, 1989;Rasmussen and Eisen, 1992;Reed, 1985), and (2) they result from a failure to cease responding following the successful completion of an action owing to a deficient response feedback mechanism (eg Baxter, 1999;Gray, 1982;Malloy, 1987;Pitman, 1991;Reed, 1977;Otto, 1990Otto, , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical assumption behind the model is that a deficit in the feedback associated with a successful performance of goal-directed behaviors leads to compulsive responses [30][31][32][33][34][35][36][37] . The model, developed by Joel and colleagues 28 , is based on operant behavior in rats.…”
Section: Introductionmentioning
confidence: 99%